On the Limit Cycles for Continuous and Discontinuous Cubic Differential Systems - Ziguo Jiang (Discrete Dynamics in Nature and Society)
We study the number of limit cycles for the quadratic polynomial differential systems x˙=-y+x2, y˙=x+xy having an isochronous center with continuous and discontinuous cubic polynomial perturbations. Using the averaging theory of first order, we obtain that 3 limit cycles bifurcate from the periodic orbits of the isochronous center with continuous perturbations and at least 7 limit cycles bifurcate from the periodic orbits of the isochronous center with discontinuous perturbations. Moreover, this work shows that the discontinuous systems have at least 4 more limit cycles surrounding the origin than the continuous ones.